Quantitative genetic analysis for meat tenderness trait in Polled Nellore cattle - Letícia Mendes de Castro (Revista Ciência Agronômica, 2014)
The aim of the present study was to analyze the interrelationships among the variables and also estimate the genetic correlations between tenderness (WBSF), growth (ILW, FLW and ADG) and carcass (BF, RF and LMA) features. Other purpose was to identify individuals who were more likely to be carriers of favorable genes for tenderness. Growth, carcass and tenderness data from 415 Polled Nellore animals was analyzed. Factor analysis and canonical correlations were used to analyze the phenotypic relationships. The covariance components and genetic parameters were estimated using Gibbs Sampling method. Lack of phenotypical correlations between the WBSF and the other traits were observed. The genetic correlations between WBSF and the other evaluated traits were of a low magnitude, with values of -0.15; -0.18; -0.13; 0.10; -0.12 and 0.18, between WBSF and ILW, FLW, ADG, BF, RF and LMA, respectively. The results support the conclusion that tenderness selection will not affect the selection of other economic traits and vice-versa, but for a better knowledge of the genetic relationships between meat tenderness and other traits for Polled Nellore more studies are required. The heritability estimated for WBSF was of a low magnitude (0.11 ± 0.022). Based on the principle of probability of identical genes by ancestry individuals who were more likely to be carriers of favorable genes for tenderness were identified. Further work will include creation of a segregating population that will serve as experimental material for future gene prospecting and identification research.